Method for synchronously preparing special-shaped inorganic nanofiber membrane
Through the synchronous preparation method, a special-shaped inorganic nanofiber membrane with high-efficiency air purification performance is prepared by using polymer spun additives, acid chloride precursors and silicon oxide precursors, combined with electrospinning and high-temperature calcining technology, which solves the problem of insufficient breathability and separation efficiency of fiber membranes in the prior art, and is especially suitable for high-temperature environments.
Patent Information
- Application Number
- CN202411854493.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Existing gas-purified nanofiber membranes have challenges in improving the breathable performance and separation efficiency of fiber membranes, especially in high temperature environments.
The synchronous preparation method is adopted to form a spinning solution by mixing a specific proportion of polymer spun spun agent, acid chloride precursor, silicon oxide precursor and volatile solvent. Then, electrospinning technology is used to spin under the environment of controlling temperature and humidity, and a special-shaped inorganic nanofiber membrane is obtained by heating and calcining.
The prepared special-shaped inorganic nanofiber membrane has good air purification performance, can efficiently intercept particulate matter such as PMX (x=0.3, 0.5, 1.0, 2.5, 5.0, 10), and has low filtration resistance, which is suitable for air purification in high-temperature environments.
Smart Images

Figure CN119565388A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of air purification membrane preparation, and relates to a method for synchronously preparing a special-shaped inorganic nanofiber membrane. Background Art
[0002] Air purification is essential for passive pollution control and human health protection in advanced manufacturing. The air permeability and separation performance of gas purification materials are core technical indicators related to process energy consumption and efficiency, and are also the main target direction for the development of gas purification materials. Nanofiber membranes have the characteristics of high specific surface area and high porosity, and have become one of the main methods for manufacturing high-efficiency air purification materials. At present, gas purification nanofiber membranes with special fiber structures, such as spider web nanofiber membranes (CN104562444A), effectively improve the physical interception ability of particulate matter, and to a certain extent achieve high-efficiency air filtration. However, due to the limitations of the cross-sectional morphology and stacking density of electrospun fibers, it is still an important challenge to simultaneously improve the air permeability and separation efficiency of fiber membranes. Summary of the invention
[0003] The present invention solves the above-mentioned deficiencies and problems in the prior art, provides a method for simultaneously preparing a high-efficiency, low-resistance special-shaped inorganic nanofiber membrane, and has a simple preparation process, and can be applied to air purification in high-temperature environments.
[0004] The technical solution of the present invention is: A method for synchronously preparing a shaped inorganic nanofiber membrane, wherein the mass ratio of a polymer spinning aid, an acid chloride precursor, a silicon oxide precursor solution and a volatile solvent is 5:(0.5-20):(0.5-100):50; rod-shaped and ribbon-shaped structural fibers are mixed, the diameter of the rod-shaped fibers ranges from 300 to 500 nm, the width of the ribbon-shaped fibers ranges from 750 to 1640 nm, and the thickness ranges from 90 to 110 nm. The specific operation includes the following steps: (1) Slowly pouring polymer particles into a desolvent, heating at 60-90°C, and fully stirring to obtain a polymer spinning aid, slowly pouring an acid chloride into a volatile solvent, and fully stirring to obtain an acid chloride precursor, slowly pouring a silicon oxide precursor into the solvent, and fully stirring to obtain a silicon oxide precursor, mixing the polymer spinning aid, the acid chloride precursor, and the silicon oxide precursor in a certain proportion, and stirring evenly at room temperature to obtain a spinning solution; (2) Using electrospinning technology, spinning the spinning solution at a certain temperature and humidity environment, at a certain injection speed, spinning voltage and receiving distance, to obtain a composite fiber containing a polymer additive, an acid chloride precursor and a silicon oxide precursor; (3) The composite fiber containing the polymer spinning aid, the acid chloride precursor and the silicon oxide precursor in step (2) is subjected to high temperature calcination according to a certain temperature increase program to obtain the shaped inorganic fiber membrane.
[0005] The polymer spinning aid in step (1) of the present invention includes one or more of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene oxide, polyvinyl butyral, and polyethylene glycol; The acidic chloride precursor in step (1) of the present invention includes one or more of hydrogen chloride, ammonium chloride, stannous chloride, stannic chloride and zinc chloride.
[0006] The silicon oxide precursor in step (1) of the present invention includes one or more of methyl orthosilicate and ethyl orthosilicate.
[0007] The solvent in step (1) of the present invention includes one or more of water, methanol, ethanol, isopropanol and n-butanol.
[0008] During the stirring and dissolving process in step (1) of the present invention, the temperature is from room temperature to 100° C., and the stirring time is 0.1 to 10 h.
[0009] The spinning temperature in step (2) of the present invention is 25-35°C, the humidity is 30%-45%, the propulsion speed of the spinning solution is 0.5-1.5 mL / h, the spinning voltage is 10-20 kV, and the distance from the spinning needle of the electrospinning machine to the receiving plate is 5-20 cm.
[0010] The medium-high temperature calcination process in step (3) of the present invention is: increasing the temperature from room temperature to 600-1000°C at a rate of 0.5-15°C / min, and then keeping the temperature for 1-2 hours.
[0011] The special-shaped inorganic nanofiber membrane prepared by the present invention can be used for intercepting PM.
[0012] Beneficial effects: The prepared inorganic nanofiber membrane has a mixture of rod-shaped and ribbon-shaped structural fibers, and the fiber diameter and membrane pore size can be controlled by changing the condition parameters. The prepared nanofiber membrane exhibits good air purification performance and has a good performance on PM X (x=0.3, 0.5, 1.0, 2.5, 5.0, 10) and other particles have excellent retention performance and low filtration resistance. They can be used in the field of gas purification and have broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is an electron microscope image of the microstructure of the shaped inorganic nanofiber membrane prepared simultaneously in Example 1.
[0014] Figure 2This is the electron microscope image of the microstructure of the shaped inorganic nanofiber membrane prepared simultaneously in Example 2.
[0015] Figure 3 This is the electron microscope image of the microstructure of the shaped inorganic nanofiber membrane prepared simultaneously in Example 3.
[0016] Figure 4 This is an electron microscope image of the microstructure of the shaped inorganic nanofiber membrane prepared simultaneously in Example 4.
[0017] Figure 5 This is the electron microscope image of the microstructure of the shaped inorganic nanofiber membrane prepared simultaneously in Example 5.
[0018] Figure 6 This is an electron microscope image of the microstructure of the shaped inorganic nanofiber membrane prepared simultaneously in Example 6.
[0019] Figure 7 This is the fiber diameter distribution spectrum of the shaped inorganic nanofiber membranes prepared simultaneously in Examples 1 to 5.
[0020] Figure 8 This is the pore size distribution spectrum of the shaped inorganic nanofiber membranes prepared simultaneously in Examples 1 to 5.
[0021] Fig. 9 The PM was prepared by simultaneously preparing the shaped inorganic nanofiber membrane in Example 7. X Filtration performance evaluation spectrum of (x=0.3, 0.5, 1.0, 2.5,5.0, 10).
[0022] Fig.10 The PM was prepared by simultaneously preparing the shaped inorganic nanofiber membrane in Example 7. 0.3 Spectrum for evaluating the cyclic filtration performance. DETAILED DESCRIPTION
[0023] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0024] The present invention provides a method for synchronously preparing a special-shaped inorganic nanofiber membrane. Example 1
[0025] A method for synchronously preparing a shaped inorganic nanofiber membrane comprises the following steps: Preparation of polymer spinning aid: Take 10 g of 1788 model polyvinyl alcohol particles and slowly pour them into a conical flask containing 90 g of water. After stirring and swelling at room temperature for about 5 hours, continue stirring at 90 °C for 5 hours until the solid is completely dissolved. Put it in a 90 °C oven and let it stand for 12 hours. Cool it to room temperature to obtain a polyvinyl alcohol solution with a mass ratio of polymer material to solvent of 1:10. Preparation of acid chloride precursor solution and silicon oxide precursor solution: 1.5 g of tin tetrachloride crystals were poured into a beaker containing 4.5 g of ethanol and stirred at room temperature for 0.5 h to obtain an acid chloride precursor solution; 10.4 g of tetraethyl orthosilicate was poured into a beaker containing 4.45 g of deionized water and stirred at room temperature for 2 h to obtain a silicon oxide precursor solution; 55 parts of polymer spinning aid, 0.5 parts of acid chloride precursor solution and 0.5 parts of silicon oxide precursor solution were mixed and stirred at room temperature to obtain an electrospinning precursor solution with a mass ratio of polymer spinning aid, acid chloride precursor, silicon oxide precursor and solvent of 5:0.5:0.5:50; Electrospinning membrane: The temperature during electrospinning was 25 °C, the humidity was 30%, the propulsion speed of the electrospinning solution was 0.5 mL / h, the spinning voltage was 10 kV, and the distance from the spinning needle of the electrospinning machine to the receiving plate was 5 cm. Calcination: The obtained composite fiber was heated from room temperature to 600 °C at a rate of 0.5 °C / min and kept at this temperature for 1 h.
[0026] Figure 1 The obtained synchronously prepared shaped inorganic nanofiber membrane had an average diameter of 300 nm for the rod-shaped fibers, an average width of 750 nm for the ribbon-shaped fibers, an average thickness of 100 nm, and an average pore size of 1.6 μm. Example 2
[0027] Preparation of polymer spinning aid: Take 10 g of polyvinyl butyral granules and slowly pour them into a conical flask containing 90 g of ethanol. After stirring and swelling at room temperature for about 5 h, continue stirring at 90 °C for 5 h until the solid is completely dissolved. Put it in a 90 °C oven and let it stand for 12 h. Cool it to room temperature to obtain a polyvinyl alcohol solution with a mass ratio of polymer material to solvent of 1:10. Preparation of acid chloride precursor solution and silicon oxide precursor solution: 1.5 g of tin dichloride crystals were poured into a beaker containing 4.5 g of ethanol and stirred at room temperature for 0.5 h to obtain an acid chloride precursor solution; 10.4 g of methyl orthosilicate was poured into a beaker containing 4.45 g of deionized water and stirred at room temperature for 2 h to obtain a silicon oxide precursor solution; 55 parts of polymer spinning aid, 20 parts of acid chloride precursor solution and 100 parts of silicon oxide precursor solution were mixed and stirred at room temperature to obtain an electrospinning precursor solution with a mass ratio of polymer spinning aid, acid chloride precursor, silicon oxide precursor and solvent of 5:20:100:50; Electrospinning membrane: The temperature during electrospinning was 25-35 °C, the humidity was 45%, the propulsion speed of the electrospinning solution was 1.5 mL / h, the spinning voltage was 14 kV, and the distance from the spinning needle of the electrospinning machine to the receiving plate was 25 cm. Calcination: The obtained composite fiber was heated from room temperature to 1000 °C at a rate of 15 °C / min and kept at this temperature for 2 h.
[0028] Figure 2 The obtained synchronously prepared shaped inorganic nanofiber membrane had an average diameter of 380 nm for the rod-shaped fibers, an average width of 1170 nm for the ribbon-shaped fibers, an average thickness of 110 nm, and an average pore size of 1.7 μm. Example 3
[0029] Preparation of polymer spinning aid: Take 10 g of polyvinyl butyral granules and slowly pour them into a conical flask containing 90 g of n-butanol. After stirring and swelling at room temperature for about 5 h, continue stirring at 90 °C for 5 h until the solid is completely dissolved. Put it in a 90 °C oven and let it stand for 12 h. Cool it to room temperature to obtain a polyvinyl alcohol solution with a mass ratio of polymer material to solvent of 1:10. Preparation of acid chloride precursor solution and silicon oxide precursor solution: 1.5 g of hydrogen chloride is taken as the acid chloride precursor solution; and 10.4 g of methyl orthosilicate is poured into a beaker containing 4.45 g of deionized water, and stirred at room temperature for 2 h to obtain a silicon oxide precursor solution; 55 parts of polymer spinning aid, 15 parts of acid chloride precursor solution and 60 parts of silicon oxide precursor solution are mixed, and stirred at room temperature to obtain an electrospinning precursor solution with a mass ratio of polymer spinning aid, acid chloride precursor, silicon oxide precursor and solvent of 5:15:60:50; Electrospinning film preparation: The temperature during electrospinning is 30 °C, the humidity is 35%, the propulsion speed of the electrospinning solution is 1.15 mL / h, the spinning voltage is 14 kV, and the distance from the spinning needle of the electrospinning machine to the receiving plate is 25 cm. Calcination: The obtained composite fiber was heated from room temperature to 800 °C at a rate of 10 °C / min and kept at this temperature for 1 h.
[0030] Figure 3 The obtained synchronously prepared shaped inorganic nanofiber membrane had an average diameter of 350 nm for the rod-shaped fibers, an average width of 1410 nm for the ribbon-shaped fibers, an average thickness of 100 nm, and an average pore size of 1.73 μm. Example 4
[0031] The preparation of the acid chloride precursor solution and the silicon oxide precursor solution was changed to: 1.5 tin tetrachloride crystals were poured into a beaker containing 4.5 g of ethanol, and stirred at room temperature for 0.5 h to obtain an acid chloride precursor solution; 10.4 g of methyl orthosilicate was poured into a beaker containing 4.45 g of deionized water, and stirred at room temperature for 2 h to obtain a silicon oxide precursor solution; 55 parts of a polymer spinning aid, 10 parts of an acid chloride precursor solution, and 70 parts of a silicon oxide precursor solution were mixed, and stirred at room temperature to obtain an electrospinning precursor solution with a mass ratio of polymer spinning aid, acid chloride precursor, silicon oxide precursor, and solvent of 5:10:70:50; Electrospinning membrane: The temperature during electrospinning was 25 °C, the humidity was 30%, the propulsion speed of the electrospinning solution was 1 mL / h, the spinning voltage was 13 kV, and the distance from the spinning needle of the electrospinning machine to the receiving plate was 12 cm. Calcination: The obtained composite fiber was heated from room temperature to 800°C at a rate of 5°C / min and kept at that temperature for 1 h. The other steps were completely consistent with those in Example 1.
[0032] Figure 4The obtained synchronously prepared shaped inorganic nanofiber membrane had an average diameter of 340 nm for the rod-shaped fibers, an average width of 1600 nm for the ribbon-shaped fibers, an average thickness of 100 nm, and an average pore size of 1.87 μm. Example 5
[0033] The preparation of the acid chloride precursor solution and the silicon oxide precursor solution was changed to: 1.5 tin tetrachloride crystals were poured into a beaker containing 4.5 g of ethanol, and stirred at room temperature for 0.5 h to obtain an acid chloride precursor solution; 10.4 g of methyl orthosilicate was poured into a beaker containing 4.45 g of deionized water, and stirred at room temperature for 2 h to obtain a silicon oxide precursor solution; 55 parts of a polymer spinning aid, 30 parts of an acid chloride precursor solution, and 70 parts of a silicon oxide precursor solution were mixed, and stirred at room temperature to obtain an electrospinning precursor solution with a mass ratio of polymer spinning aid, acid chloride precursor, silicon oxide precursor, and solvent of 5:30:70:50; Electrospinning membrane: The temperature during electrospinning was 30 °C, the humidity was 40%, the propulsion speed of the electrospinning solution was 0.95 mL / h, the spinning voltage was 12 kV, and the distance from the spinning needle of the electrospinning machine to the receiving plate was 13 cm. Calcination: The obtained composite fiber was heated from room temperature to 800°C at a rate of 15°C / min and kept at that temperature for 1 h. The other steps were completely consistent with Example 1.
[0034] Figure 5 The obtained synchronously prepared shaped inorganic nanofiber membrane had an average diameter of 330 nm for the rod-shaped fibers, an average width of 1640 nm for the ribbon-shaped fibers, an average thickness of 100 nm, and an average pore size of 3.2 μm. Example 6
[0035] The preparation of the acid chloride precursor solution and the silicon oxide precursor solution was changed to: take 1.5 tin dichloride crystals and pour them into a beaker containing 4.5 g of ethanol, stir at room temperature for 0.5 h to obtain an acid chloride precursor solution; take 10.4 g of tetraethyl orthosilicate and pour it into a beaker containing 4.45 g of deionized water, stir at room temperature for 2 h to obtain a silicon oxide precursor solution; 55 parts of polymer spinning aids, 30 parts of acid chloride precursor solution and 70 parts of silicon oxide precursor solution were mixed, and stirred at room temperature to obtain an electrospinning precursor solution with a mass ratio of polymer spinning aids, acid chloride precursors, silicon oxide precursors and solvent of 5:30:70:50; Electrospinning membrane: The temperature during electrospinning was 30 °C, the humidity was 40%, the propulsion speed of the electrospinning solution was 1 mL / h, the spinning voltage was 15 kV, and the distance from the spinning needle of the electrospinning machine to the receiving plate was 16 cm. Calcination: The obtained composite fiber was heated from room temperature to 600°C at a rate of 5°C / min and kept at that temperature for 1 h. The other steps were completely consistent with those in Example 1.
[0036] Figure 6 The obtained shaped inorganic nanofiber membrane is prepared synchronously. Example 7
[0037] The shaped inorganic nanofiber membranes prepared in Examples 1 to 5 were used to filter particles with a size of PM X NaCl particles with a velocity of 5.33 cm / s (x=0.3, 0.5, 1.0, 5.0, 10). Fig. 9 The results showed that PM X The filtration efficiency of (x=0.3, 0.5, 1.0,5.0, 10) exceeds 99.96%; Fig.10 As shown in Figure 2, the shaped nanofiber membrane exhibited excellent PM 0.3 Cyclic filtration performance, the shaped inorganic nanofiber membrane prepared in Example 5 for PM 0.3 The filtration efficiency remained basically unchanged during the 20 filtration cycles, and the filtration pressure drop increased from 67 Pa to 87 Pa.
Claims
1. A method for synchronously preparing a shaped inorganic nanofiber membrane, characterized in that: A polymer spinning aid, an acid chloride precursor, and a silicon oxide precursor are dissolved in a volatile solvent, and the mixed solution of the polymer spinning aid and the precursor is spun into a film by using an electrostatic spinning technology, and a shaped inorganic nanofiber membrane is obtained by high-temperature calcination. The specific operation includes the following steps: (1) Slowly pouring polymer particles into a desolvent, heating at 60-90°C, and fully stirring to obtain a polymer spinning aid; slowly pouring an acid chloride into a volatile solvent, and fully stirring to obtain an acid chloride precursor; slowly pouring a silicon oxide precursor into a solvent, and fully stirring to obtain a silicon oxide precursor; mixing the polymer spinning aid, the acid chloride precursor, and the silicon oxide precursor in a certain proportion, and stirring evenly at room temperature to obtain a spinning solution; (2) Using electrospinning technology, spinning the spinning solution at a certain temperature and humidity environment, at a certain injection speed, spinning voltage and receiving distance, to obtain a composite fiber containing a polymer additive, an acid chloride precursor and a silicon oxide precursor; (3) The composite fiber containing the polymer spinning aid, the acid chloride precursor and the silicon oxide precursor described in step (2) is calcined at high temperature according to a certain temperature rising program to obtain a shaped inorganic fiber membrane.
2. The method for synchronously preparing a shaped inorganic nanofiber membrane according to claim 1, characterized in that: The polymer spinning aid in step (1) includes one or more of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene oxide, polyvinyl butyral, and polyethylene glycol.
3. The method for synchronously preparing a shaped inorganic nanofiber membrane according to claim 1, characterized in that: The acid chloride precursor in step (1) includes one or more of hydrogen chloride, ammonium chloride, stannous chloride, stannic chloride, and zinc chloride; the silicon oxide precursor includes one or more of methyl orthosilicate and ethyl orthosilicate; and the volatile solvent includes one or more of water, methanol, ethanol, isopropanol, and n-butanol.
4. The method for synchronously preparing a shaped inorganic nanofiber membrane according to claim 1, characterized in that: In step (1), the mass ratio of the polymer spinning aid, the acid chloride precursor, the silicon oxide precursor and the solvent is 5:(0.5-20):(0.5-100):
50.
5. The method for synchronously preparing a shaped inorganic nanofiber membrane according to claim 1, characterized in that: In step (2), the spinning temperature is 25-35°C, the humidity is 30%-45%, the propulsion speed of the spinning solution is 0.5-1.5 mL / h, the spinning voltage is 10-20 kV, and the distance from the spinning needle of the electrospinning machine to the receiving plate is 5-20 cm.
6. The method for synchronously preparing a shaped inorganic nanofiber membrane according to claim 1, characterized in that: The high temperature calcination process in step (3) is as follows: the temperature is raised from room temperature to 600-1000°C at a rate of 0.5-15°C / min, and then kept at this temperature for 1-2 h.
7. The method for synchronously preparing a shaped inorganic nanofiber membrane according to any one of claims 1 to 6, characterized in that: The shaped inorganic nanofiber membrane is mixed with rod-shaped and ribbon-shaped structural fibers, the diameter of the rod-shaped fibers ranges from 300 to 500 nm, the width of the ribbon-shaped fibers ranges from 750 to 1750 nm, and the thickness ranges from 90 to 110 nm. The shaped inorganic nanofiber membrane is used for filtering dust particles.
Citation Information
Patent Citations
Electrostatic spraying nano-cobweb waterproof moisture-permeable film and preparation method thereof
CN104562444A
High temperature resistance and corrosion resistance inorganic filtration fiber membrane and preparation method thereof
CN107604537A
Preparation method of flexible porous SiO2 nanofiber membrane with both high specific surface area and large aperture
CN113846418A
Preparation method of flexible composite nanofiber membrane with core-shell structure
CN113981618A
Flexible inorganic nanofiber composite scaffold and preparation method thereof
CN114588317A
Cited By
A belt-shaped silica nanofiber membrane and a method for preparing the same
CN122669549A